Pengaruh Tingkat Kebisingan Akibat Aktivitas Lalulintas: (Studi Kasus Jalan Lintas Sekolah Dasar Negeri 02 Kendari, Sulawesi Tenggara) - Fuji Hastuti, Fransisca; Sumarlin, Sumarlin; Assiddieq, Moch. (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2024)
This research examines the volume of traffic and noise at public elementary school 02 Kendari. Traffic volume is the number of vehicles passing a certain location on a road section in a certain time period. The volume applied is the peak hour volume. Peak hour volume is the number of vehicles passing through traffic flow during one hour of the day which is characterized by the highest traffic flow. The problems that arise in Kendari City regarding transportation, especially on Jalan Christina Marta Tiahahu, are not only traffic jams, but also noise problems. Noise is a source of sound that interferes with human hearing perception. Noise level is a metric that measures noise intensity in decibels (dB). The dB value is a unit of noise intensity in class A, namely the class that corresponds to the normal human response. The problem in this research is the volume level and noise volume. The aim of the research is to determine vehicle volume and noise levels. The method used is a direct data collection method for vehicle volume, for noise using a tool called a sounds level meter and questionnaire data for additional noise.